Kajian Kriminologi Terhadap Minuman Tradisional Beralkohol (Sopi) Di Desa Mngeswaen - Solissa, Moksen Doyan; Sopacua, Margie Gladies; Salamor, Anna Maria (Faculty of Law, Universitas Pattimura, 2024)
Introduction: Criminology is the study of crime and criminal acts. The Maluku province has a local alcohol soothing drink, namely, Sopi which is the result of calming sap or sweet liquid obtained from plant stems, and is produced by people for generations on various islands in Maluku. Sopi is produced from the mayang tree (sageru) and is then processed traditionally using the knowledge that was also passed down by our predecessors. For this reason, sopi is always present in the traditional rituals of the Maluku people.Purposes of the Research: To analyze and discuss the influence of alcoholic beverages (sopi) on crime in the Mngeswaen Village and the efforts made by the Police in tackling traditional alcoholic beverages (sopi) in the Mngeswaen Village.Methods of the Research: The research method used is empirical legal research, namely a type of legal research that analyzes and examines the operation of law in society. qualitative analysisResults of the Research: The results of the study show that the causes of the people of Mngeswaen Village consuming sopi are due to several reasons, namely community habits, alcohol addiction, feeling agitated and depressed, generating a spirit of mutual cooperation, social climbers, strengthening friendships and calming the mind to sleep soundly. The adverse effects of drinking sopi include fights between the residents of Mngeswaen Village. Countermeasures against the adverse effects caused by traditional alcoholic beverages (sopi) are carried out through preventive and repressive efforts by the local police, as well as by the village government, traditional leaders, religious leaders, educational leaders, health leaders as well as community leaders.